Condition of pro-oxidant and antioxidant systems in guinea pigs’ lungs under the condition of immobilization stress - Kryvko, Yurij; Soguiko, Yurij; Hot, Iryna; Antonenko, Yuliia; Baida, Mariana; Kovalska, Marta (Journal of Education, Health and Sport, 2021)
We have investigated the results of alterations in indices of pro-oxidant (conjugated diene and malondialdehyde) and antioxidant (superoxide dismutase, ceruloplasmin, catalase) systems in guinea pigs’ lungs under the conditions of immobilization stress. The experiment was conducted on 40 female guinea pigs weighing 0.18-0.20 kg. The animals were divided into 4 groups, each contained 10 guinea pigs: I – intact guinea pigs (control), II–guinea pigs with model of IS on1st day of experiment;Ш–animals on 2nd day of experiment;IV- group of animals on 34th day of experimental model of IS. The results of our experimental work showed a significant accumulation of lipid peroxidation products in the lung`s tissure in different periods (on 1st, 2nd and 34th days) of immobilization stress. The state of antioxidant defence was characterized by moderate decrease of inzymes activity (superoxide dismutase, catalase and ceruloplasmin). disorders of balance between pro-oxidant and antioxidant systems couse oxidative stress development.